Characteristics of potential head injuries across three FIFA Futsal World Cups from 2016 to 2024: A video analysis study - Lima, Y.; Atay, Y.; Serner, A.; Peek, K.; Karaçoban, L. (Journal of Science and Medicine in Sport, 2026)
Objectives To evaluate potential head injuries across three consecutive FIFA Futsal World Cups held between 2016 and 2024.